Drug Delivery across Biological Barriers - Tennikova, Tatiana B.; Korzhikova-Vlakh, Evgenia G. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint is a collection of original articles and reviews in the field of modern drug delivery systems and strategies for efficient drug transport across various biological barriers, including the blood-brain barrier, mucosal and endothelial barriers, and cell membranes.